MIXED EFFECT OF SOME OF HEAVY METALS ON SURVIVAL OF FISH LIZA ABU (HICKEL 1843) - AL-DOGHACHI, M.A.R. (Iraqi Journal of Aquaculture, 2022)
Effect some of heavy metals ( Copper , Lead , Zinc) on survival of fish Liza abu (Hickel ) have been studied and compared with mixed effect of two elements in same concentrations (1 , 3, 5) ppm. Synergism effect observed on mixed of (Cu + Pb , Cu + Zn ) while Antagonism effect at mixture of (Zn + Pb) . All of these effects order as follows : Cu + Zn> Cu + Pb > Pb + Zn.